Deficiency of caspase recruitment domain family, member 11 (CARD11), causes profound combined immunodeficiency in human subjects - Stepensky, Polina; Keller, Baerbel; Buchta, Mary; Kienzler, Anne-Kathrin; Elpeleg, Orly; Somech, Raz; Cohen, Sivan; Shachar, Idit; Miosge, Lisa A.; Schlesier, Michael; Fuchs, Ilka; Enders, Anselm; et al. (Journal of allergy and clinical immunology, 2013)
Profound combined immunodeficiency can present with normal numbers of T and B cells, and therefore the functional defect of the cellular and humoral immune response is often not recognized until the first severe clinical manifestation. Here we report a patient of consanguineous descent presenting at 13 months of age with hypogammaglobulinemia, Pneumocystis jirovecii pneumonia, and a suggestive family history. We sought to identify the genetic alteration in a patient with combined immunodeficiency and characterize human caspase recruitment domain family, member 11 (CARD11), deficiency. Molecular, immunologic, and functional assays were performed. The immunologic characterization revealed only subtle changes in the T-cell and natural killer cell compartment, whereas B-cell differentiation, although normal in number, was distinctively blocked at the transitional stage. Genetic evaluation revealed a homozygous deletion of exon 21 in CARD11 as the underlying defect. This deletion abrogated protein expression and activation of the canonical nuclear factor κB (NF-κB) pathway in lymphocytes after antigen receptor or phorbol 12-myristate 13-acetate stimulation, whereas CD40 signaling in B cells was preserved. The abrogated activation of the canonical NF-κB pathway was associated with severely impaired upregulation of inducible T-cell costimulator, OX40, cytokine production, proliferation of T cells, and B cell–activating factor receptor expression on B cells. Thus in patients with CARD11 deficiency, the combination of impaired activation and especially upregulation of inducible T-cell costimulator on T cells, together with severely disturbed peripheral B-cell differentiation, apparently leads to a defective T-cell/B-cell cooperation and probably germinal center formation and clinically results in severe immunodeficiency. This report discloses the crucial and nonredundant role of canonical NF-κB activation and specifically CARD11 in the antigen-specific immune response in human subjects.